2017
DOI: 10.1073/pnas.1701590114
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological dynamics of phrase-structure building during sentence processing

Abstract: Although sentences unfold sequentially, one word at a time, most linguistic theories propose that their underlying syntactic structure involves a tree of nested phrases rather than a linear sequence of words. Whether and how the brain builds such structures, however, remains largely unknown. Here, we used human intracranial recordings and visual word-by-word presentation of sentences and word lists to investigate how left-hemispheric brain activity varies during the formation of phrase structures. In a broad s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
280
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(313 citation statements)
references
References 55 publications
(98 reference statements)
29
280
1
3
Order By: Relevance
“…Similar to the interpretations by Brennan et al (2016) and Nelson et al (2017), the authors interpreted the results as showing that hierarchical linguistic structure is computed during comprehension because it improves the fit to empirical data over competitive non-hierarchical models.…”
Section: Information Measures As Additional Predictormentioning
(Expert classified)
See 3 more Smart Citations
“…Similar to the interpretations by Brennan et al (2016) and Nelson et al (2017), the authors interpreted the results as showing that hierarchical linguistic structure is computed during comprehension because it improves the fit to empirical data over competitive non-hierarchical models.…”
Section: Information Measures As Additional Predictormentioning
(Expert classified)
“…Current applications of probabilistic language models in cognitive neuroscience show that probabilistic language models can be used with hemodynamic and electrophysiological methods and allow researchers to investigate and focus on spatial fingerprints for specific linguistic computations in cortical regions (Willems et al, 2016;Henderson et al, 2016) or to compare predictions of different models against each other on the basis of same neurobiological data, be it fMRI time courses , language event-related M/EEG components (Frank et al, 2015;Wehbe et al, 2015), or spectral contents of electrophysiological signals (van Schijndel et al, 2015;Nelson et al, 2017). The studies employed language stimuli in both auditory and visual modalities and, with the exception of the studies by Frank et al (2015) and Nelson et al (2017), used language stimuli in naturalistic, narrative contexts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent neurophysiological brain activity study (Nelson et al 2017) claims to have demonstrated the neurophysiological reality of phrase structure. In the authors' opinion, their results "strongly motivate the view of language as being hierarchically structured and make it increasingly implausible to maintain the opposite nonhierarchical view" (Nelson et al 2017: E3676).…”
Section: The Emergent-generative Debatementioning
confidence: 99%